Tailoring relaxor P4bm+P21ma phases in BNT-based ceramics for enhancing comprehensive energy storage properties. (June 2023) - Wang, Hao; Li, Ziming; Zhang, Jingji; Wu, Shengyang; Du, Huiwei; Zong, Quan; Wang, Jiangying; Zhang, Yang; Bai, Wangfeng; Zheng, Peng
Abstract: Tailoring relaxor phase is an effective strategy to enhance energy-storage properties (ESP) for Bi0.5 Na0.5 TiO3 (BNT)-based ceramics. Herein, we incorporate Na0.91 Bi0.09 Nb0.94 Mg0.06 O3 (NBNM) into BNT matrix to form a solid solution of BNT- x NBNM with x = 0.1–0.4. Rietveld refinements reveal that the composition with x = 0.3 has 46% relaxor tetragonal P 4 bm phase and 54% relaxor orthorhombic P 21 ma one, thus exhibiting a large normalized energy-storage density ( W rec / E = 0.015 J kV −1 cm −2 ) and a high efficiency ( η = 87%) at 370 kV cm −1 . The optimized composition also presents superior temperature stability with a variation of <±5% in the range of 20 °C–150 °C, outstanding frequency reliability with a variation of <±4% in the range of 5 Hz–500 Hz and excellent charge-discharge properties (discharge rate of 76 ns, current density of 1032 A cm −2 and power density of 129 MW cm −3 at 250 kV cm −1 ). The results demonstrate a successful strategy to design high performance Pb-free relaxor ferroelectrics for pulsed power capacitor applications. Highlights: 0.7BNT-0.3NBNM ceramics has coexistent 46% P 4 bm phase and 54% P 21 ma phase. 0.7BNT-0.3NBNM ceramics exhibit a large W rec / E of 0.015 J kV −1 cm −2 and a high η of 87% at 370 kV cm −1 . 0.7BNT-0.3NBNM ceramics present outstanding stability over 20 °C–150 °C and 5Hz–500Hz. 0.7BNT-0.3NBNM ceramics show a fast t 0.9 of 76 ns and a large P D of 129 MW‧cm −3 at 250 kV‧cm −1 .